Fermentation ability of specific strains of Lactiplantibacillus plantarum using mango as base material - Aviles-Rivera, Yudit Aimee; Hernández-Mendoza, Adrián; Basilio Heredia, José; Mata-Haro, Verónica; Santiago-López, Lourdes; Muy-Rangel, María Dolores (Revista Mexicana de Ciencias Agrícolas, 2024)
The fermentation ability of two potentially probiotic bacteria, Lactiplantibacillus plantarum Lp6 and Lp32, was evaluated on juice from mango cv Ataulfo as a substrate. To do this, the strains (1010 CFU ml-1) were added in three levels of inoculum (1, 2, and 3%, v/v) in mango juice and incubated for 36 h at 37 °C. Samples were taken (0, 18, and 36 h) to assess bacterial growth, total soluble solids, individual sugars, pH, and titratable acidity (% lactic acid). Additionally, the effect of fermentation on the color and sugars (glucose, fructose, and sucrose) of the juice was determined. Both strains have fermentation ability and a cell growth of four logarithmic cycles after 12 h of fermentation. No differences in color were observed between fermented and unfermented juice. Lp6 and Lp32 bacteria can be used as starter cultures for the production of mango-based functional beverages.